Effects of fatigue on motor unit characteristics in isometric elbow contractions across age groups - Kuang, Huaning; Qiu, Fang; Liu, Xiaodong; Chen, Chen (Frontiers in Neuroscience, 2026)
This study aims to investigate the neuromuscular regulation mechanisms in different age groups under conditions of fatigue. A total of 50 participants aged between 10 and 80 years were recruited and divided into 11 different age groups. Each participant performed a triangular wave isometric contraction before and after fatigue. The convolution kernel compensation algorithm was employed to extract the motor unit (MU) spike trains from the biceps brachii and triceps brachii muscles. The extracted features included root mean square, mean power frequency, motor unit action potential (MUAP) peak-to-peak values, MUAP duration, recruitment threshold, derecruitment threshold, discharge frequency, and common neural drive, which were compared across age groups before and after fatigue. Significant variations in fatigue adaptation were observed among age groups, according to the study. Adults tend to recruit larger motor units to compensate for fatigue-induced strength decline. The elderly group’s discharge frequency and MU recruitment threshold, on the other hand, did not significantly change, indicating that their neuromuscular system was less able to adjust to fatigue. The child group may have relied more on discharge frequency modulation during fatigue because they displayed smaller variations in recruitment threshold. At the same time, PCA results showed that fatigue induced a greater reduction in common-drive coherence in children and older adults, suggesting that maintaining coordinated neural drive becomes more challenging during development and aging. This study clarifies the differences in neuromuscular fatigue adaptation mechanisms at different stages of life and reveals the changing patterns of MU regulation strategies across the examined age range. The resulting age-dependent MU patterns provide an important physiological reference for neurological healthcare, facilitating clearer identification and interpretation of deviations associated with neuromuscular and neurological disorders.